Optimal design of tilt integral derivative controller for a boost converter based on swarm-inspired algorithms - Adnan Mukhtar; Pyare Mohan Tiwari; Saud Alotaibi; Thabet Alzahrani; Borchala Namomsa; Mahrous Ahmed (Scientific Reports)
Abstract This article proposes a novel dual-loop control (DLC) method with a Tilt Integral Derivative (TID) Controller for output voltage regulation and inductor current regulation in a boost converter. The TID controller is designed with the aid of swarm inspired algorithms, particularly Artificial Bee Colony (ABC) and Salp Swarm Optimization (SSO). The TID Controller is a robust, and feedback type of controller and belongs to the family of fractional order controllers. This controller has several advantages, such as superior control over complex systems, improved disturbance rejection, enhanced robustness, and better transient response over conventional controllers, such as, PID. Due to the inherent instability and limited controllability, a boost converter may pose significant challenges, necessitating the use of sophisticated control methodologies. The DLC method being proposed comprises of an inner-loop for current regulation and an outer-loop for voltage regulation. The inner-loop comprises of a current sensor and a TID controller, which provide a fast transient response and overcurrent protection, while as the outer-loop comprises of a voltage sensor and a TID controller, which ensure a precise steady-state accuracy and output voltage regulation. The utilization of ABC and SSO techniques effectively address the specific challenges associated with boost converters, leading to enhanced stability and transient response. The proposed control method demonstrates efficacy through extensive simulation and experimental investigation under start-up response, step perturbations in external load, and reference voltage change. The experimentation is conducted on a laboratory prototype using dspace DS1104 control board with MPC8240 processor. The system demonstrates improved time domain specifications, with settling time of 10 ms and 6 ms during start-up, 5 ms and 4.5 ms, during load change, 6 ms and 4.5 ms during reference voltage change for output voltage and inductor current respectively under the action of SSO-based TID controller. This article presents the first documented application and development of ABC and SSO-optimized TID controllers. However, these algorithms have shown promise in other engineering applications, which suggests that they may be effective in optimizing output voltage and inductor current in boost converters as well. This research enhances the control of boost converters, making them more suitable for a range of applications in power supply, EVs, green energy systems, and battery charging.